Posted by **zam** on Wednesday, October 8, 2008 at 10:53pm.

(x^2 + 2x - 4)^2 - (x^2 - 2x - 4)^2

## Answer This Question

## Related Questions

- math i need help - What is the simplified form of each expression? 1. Alg 1 (1 ...
- pre alg - How do u find the GCF with exponets in a 7th gr. pre alg. class?
- Alg II - So in our Alg II class we're studing variables and functions, and from ...
- Alg 1 - The popultion of Medford High is 800 students & the population of ...
- math - how do i solve two step equations? Do you mean two equations in two ...
- ALG - 1 r = 1 r1 + 1 r2 for r2
- alg - 5x-10/5 ?
- alg 2 - X-4z=13 5x-4y+z=-7 -5x-5y+2z=22
- Alg - (2x/2x) + 1 == 1?
- alg - 2(-3^8-9)x9

More Related Questions